Hiperendemicidad de fasciolosis y factores de riesgo en niños de edad escolar del distrito de Orurillo, Puno - Quispe P., William (2021)
The aim of this study was to determine the association of fasciolosis in school-age children with intestinal parasites, food consumption and animal husbandry. The research was analytical, prospective, cross-sectional, and relational. In total, 295 serological and stool samples were obtained, and an epidemiological interview was carried out on children of both sexes, aged 3 to 19 years from 23 institutions of initial, primary and secondary education, with the informed consent of their parents. The serological diagnosis was made using the IgG immunoblot technique and the IgG ELISA test and the stool diagnosis was made with the rapid sedimentation technique modified by Lumbreras. Risk factors were obtained by epidemiological interview. The prevalence of fasciolosis was 11.2% (95% CI = 7.4-14.9; 33/295). Significant differences were found between educational institutions and communities of origin. Both in univariate and multivariate analyses determined that drinking well water and raising guinea pigs were associated with fasciolosis.